Nutritional Intake Education by Peers, Nutritionists, and Combinations to Changes in Nutritional Status in Adolescent Girl in School - Christiany, Irine; Mu’afiro, Adin; Waluyo, Kiaonarni Ongko; Suparji, Suparji (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Adolescents pay such close attention to their physical shape and frequently construct their own body image. Low knowledge of nutrients will have an impact on attitudes and behavior related to nutritional status in adolescents. Nutrition education can also help youth gain adolescents' knowledge. Peers are believed to be very influential as educators, so, peer nutritional education in adolescents will be felt positively and have a very significant impact on nutritional status. Aims: This study aims to determine the effect of nutrition education conducted by peers, nutrition, and a combination on the nutritional status of adolescents. Methods and Material: This research used is a quasi-experimental design using a pretest-posttest control group design.The sample consisted of 120 students with an age range of 15–18 years, selected by random sampling. Nutrition education is provided by means of lectures and discussions by peers, nutritionists, or a combination of the two for 1 meeting a week. Statistical analysis used: This study will use the paired t test. Results: The findings revealed that nutrition education delivered by peers had a p value of 0.033 and nutrition education delivered by nutritionists had a p value of 0.003, but there was no significant effect on adolescent nutritional status when nutrition education was delivered in combination with a p value of 0.317. Nutrition education provided by peers is very useful for improving the nutritional status of adolescents. Conclusions: Nutritional education provided by peers is proven to be able to have a positive impact on adolescents because peers are the axis of youth association, so that what is shared and learned by peers will be more easily accepted.